The Effectiveness of The Get Resih Application to Improve Clean and Healthy Living Behavior (CHLB) in Children - Yun Nina Ekawati; Nofrans Eka Saputra; Guspianto Guspianto; Jelpa Periantalo; Dewi Rahayu (Universitas Ahmad Dahlan, 2024)
This study aims to test the effectiveness of the Get Resih Application to increase knowledge of Clean and Healthy Living Behavior (CHLB) in children. The method used is a quasi-experimental design with a pre-post group design. The study population consists of 22 kindergarten students who were randomly selected. The sampling technique is total sampling consisting of 11 experimental group and 11 a control group. The experimental group was given the Get Resih treatment – a knowledge scale of clean and healthy living behaviors used in the pretest and posttest. The results were analyzed using independent t-test and paired t-test samples. The results showed that there was a significant increase in CHLB knowledge between pretest and posttest scores in the experimental group. Meanwhile, in the controlled group, no significant knowledge of CHLB was found. It can be concluded that the Get Resih application can increase CHLB knowledge in children.